New Wine in Old Wineskins: Hybrid Micelles of Poorly Water-soluble Drugs as a Template in Creation of Bifunctional Silica Nanocarriers - Shishmakova, Elena M.; Bolshakova, Anastasia V.; Urodkova, Ekaterina K.; Grammatikova, Natalia E.; Rudoy, Victor M.; Dement'eva, Olga V. (Pharmaceutical Research - Recent Advances and Trends Vol. 4, 2024)
Aims: Development of a general concept for creating mesoporous silica nanocontainers (MSNs), that ensures the combination of the stages of their sol-gel synthesis and loading with several drugs (including hydrophobic ones) and evaluation of the prospects of creation of bionanocomposites based on such MSNs. Methodology: When creating MSNs, hybrid templates are used, which are micelles of amphiphilic drugs with a hydrophobic biologically active compound (curcumin, quercetin, etc.) solubilized in them. During the study, two groups of problems were solved. The first of them consisted of studying the features of the formation of such templates, establishing the influence of the conditions of MSNs synthesis on their morphology and loading capacity, as well as determining the factors that control the rate of encapsulated drugs’ release. The second group includes problems related to the creation of nanocomposites based on MSNs and the biocompatible polysaccharide sodium alginate, the study of their properties, and the assessment of biological activity. Results: Solubilization of hydrophobic bioactive compounds in micelles of amphiphilic drugs (e.g. antiseptics), belonging to the class of cationic surfactants, is a thermodynamically favorable process that greatly (up to 80 times) enhances the solubility of such compounds in water. Sol-gel synthesis on such hybrid templates leads to the formation of bifunctional MSNs characterized by a narrow size distribution, a pronounced porous structure, and a high loading capacity. The release rate of both encapsulated drugs can be controlled by the changing medium pH. The possibility of creating antibacterial nanocomposites with prolonged action was demonstrated when using MSNs obtained on micelles of the amphiphilic antiseptic miramistin with solubilized quercetin as a model. Conclusion: The proposed approach to creating bifunctional MSNs can be applied to different compounds. It is of special interest from the point of view of creating new biomedical materials (primarily for dentistry and tissue regeneration).